Post Mortem Reputation, Compensatory Gifts and Equal Bequests - Michael Lundholm; Henry Ohlsson (Uppsala University, Department of Economics, 1999)
The empirical evidence suggests that parents use inter vivos gifts (i.e., transfers of tangible and financial property) to compensate less well off children whereas post mortem bequests are divided equally among siblings. We study a theoretical model assuming, first, that the amounts given is private information, only known to the donor and the donee, while the amounts bequeathed is public information. Second, we assume that parents care about the reputation that their bequest behavior will leave them after their death. More specifically, this reputation is deteriorating in the difference in amounts inherited. We show that, given optimal choice of altruistic parents is compensatory gifts and equal bequests.
urn:nbn:se:uu:diva-2441
Keywords: D10; D31; D63; D64; 330; altruism; bequests; inheritances; gifts; equal division; post mortem reputation; social norm; information; Intergenerationale Übertragung; Erbe; Familienökonomik; Overlapping Generations; Altruismus; Theorie